Problems of Somatic Pathology in Children with Autistic Spectrum Disorders - Yu.V. Pakulova-Trotska; S.L. Niankovskyi (Zaslavsky O.Yu., 2016)
Autistic spectrum disorders (ASD) - a complex deviation that is caused by developmental disorders of the brain and is characterized by severe comprehensive deficit of social interaction and communication, as well as restricted interests and obsessive-compulsive states. Incidence in the population is 1 : 63. Most of people with ASD have concomitant somatic problems, whose incidence is higher than in the population as a whole. Allergological and gastroenterological diseases may significantly worsen ASD manifestations. Detection and elimination of physical problems improves functioning of people with ASD. An examination of 21 children with ASD found the most common somatic pathology (atopic dermatitis, constipation, impaired feeding behavior and, as a result, deviations of physical development) and its influence on children's behavior. Directions for further study of physical problems in children with ASD were determined.